PENERAPAN JURNALISME BERPERSPEKTIF GENDER DALAM BERITA PROSTITUSI ONLINE VANESSA ANGEL DI DETIK.COM - Rahmawati Latief; Faradhillah Azis (Fakultas Dakwah dan Komunikasi, 2019)
This research aims to find out how to apply gender perspective journalism to the aspect of gender sensitivity, aspects of writing techniques, and aspects of the reportage technique in the news of the online prostitution of Vanessa Angel in detik.com. The study used descriptive quantitative research with the approach of content analysis method. The results showed that the news of the online prostitution of Vanessa Angel in detik.com still did not fully apply gender perspective journalism particularly in the category gender sensitivity or the alignments of women until the women's coverage is still represented as a discriminatory object.